The feasibility of 12-year compulsory education policy in Malaysia from the perspective of B40 parents - Juliana Mohd Janjang; Mohamed Yusoff Mohd Nor; Aida Hanim A. Hamid (Institute of Advanced Engineering and Science, 2023)
Compulsory education in Malaysia is limited to primary education within 6 years compared to the international level (8 to 12 years). There is concern that because other levels of education are still optional, enrolment will fall. It is suggested to prolong compulsory education to a total of 12 years to ensure that students obtain preschool and secondary education. As a result, a survey of 278 B40 parents or socioeconomic parents with household income less than RM4850 in urban and rural primary schools was conducted to determine the level of understanding, readiness, and acceptance of the feasibility of implementing the 12-year compulsory education policy. A valid and reliable questionnaire instrument was administered online and subsequently analyzed using SPSS Version 26. The study’s results revealed that the level of understanding (M=3.564, SD=0.462), readiness (M=3.529, SD=0.491), and their acceptance (M=3.568, SD=0.495) were very high and there were no significant differences for each dimension based on location. In principle, this indicates that B40 parents support the intention to expand our country’s policy on compulsory education. Policymakers could employ this finding to modify the current compulsory education policy in the future.